(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The constitutional legitimacy of the discipline adopted in Italy to deal with the CoViD-19 emergency must be evaluate on the basis of the principle of legality and reasonableness. However, there are also assessments in terms of opportunities to object to. The evolution of the said discipline highlights how legality and opportunity have both played an important role in government choices.